Isolation and Identification of Escherichia coli from various foodstuffs and their Resistance against clinically significant antibiotics - Goyal, Pankaj; Chauhan, Abhishek (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
A total of fifty-seven ready-to-eat food samples were collected from different locations of NCR, India to explore the prevalence of Escherichia coli in some commonly offered foodstuffs and to assess the antibiotic resistance and susceptibility profile of these isolated bacterial contaminants. These samples were characterized microbiologically for the presence of Escherichia coli. Out of fifty-seven collected samples, only twenty-four were found to have Escherichia coli. These isolates were morphologically and biochemically identified and were then evaluated for their resistance and susceptibility profile against twenty antibiotics for several clinical implications. This study shows the clear picture of prevalence of resistance among Escherichia coli isolates. Isolates were found to have variable susceptibilities against the antibiotics used in the study. Vancomycin was the drug of concern because of its non inhibitory nature. Antibiotics evaluated in this study were shown to have mild-to-moderate inhibitory activity. Also determined the multidrug resistance among Escherichia coli isolates. It has been observed that all the isolates were having a sort of susceptibility on the scale of 0-1. A number of strains isolated demonstrated the variable nature of MAR against the evaluated antibiotics.